The Quran and Family Concept in Modern Southeast Asia: Case Study of Indonesia and Malaysia - Kusmana, Kusmana (el Harakah: Jurnal Budaya Islam, 2022)
This article discusses how the Quran is used to conceptualize family in Islam in modern Southeast Asia, particularly in Indonesia and Malaysia. It examines how the concept is formulated, institutionalized, and practiced. This study is important due to the need to clarify the existing irony. On one side, the family concept is the most resistant to change, on the other side, many changes in social forces and practices require response since the modern era began in 1800. It is interesting how these contradictory powers interact with one another, where the Quran is used as the fundamental source. Using a descriptive and analytic method, the discussion is organized as follows: the study context, topic limitation, Quranic norms, family administration, education, modernity, and patriarchy issue. The study finds that the state and Muslim scholars in both countries have been trying to re-use the Quran in contextualizing the family ideal concept to meet the demand of age. In Malaysia, they take the policy stuck to the accepted medieval understanding of Islam faithfully, whereas in Indonesia, they are a bit inclusive, accepting different views and practices; even though both have similar understanding of Islam, Shāfi’iyyah in Islamic law and Ash-Ashariyyah in theology. Dalam Islam di Asia Tenggara modern, Quran digunakan untuk konseptualisasi keluarga khususnya di Indonesia dan Malaysia. Studi ini mengkaji konsep tersebut dirumuskan, dilembagakan, dan dipraktikkan. Penelitian ini penting karena memperjelas ironi yang ada. Di satu sisi, konsep keluarga paling tahan terhadap perubahan, di sisi lain, ada banyak perubahan kekuatan dan praktik sosial yang membutuhkan respons, sejak 1800. Sangat menarik untuk dibahas kekuatan yang kontradiktif ini berinteraksi satu sama lain, dimana Quran digunakan sebagai sumber inspirasi. Dengan metode deskriptif dan analitik, penelitian diatur sebagai berikut: konteks kajian, keterbatasan topik, norma Quran, administrasi keluarga, lembaga pendidikan, modernitas, dan isu patriarki. Studi menemukan bahwa negara dan cendekiawan Muslim di kedua negara telah berupaya menggunakan kembali Quran dalam kontekstualisasi konsep ideal keluarga untuk memenuhi tuntutan usia. Di Malaysia, mereka mengambil kebijakan yang melekat pada pemahaman abad pertengahan yang diterima tentang Islam, sedangkan di Indonesia lebih inklusif, menerima pandangan dan praktik yang berbeda, meskipun keduanya memiliki pemahaman serupa tentang Islam, yaitu Shāfi'iyyah dalam hukum Islam, dan Ash-Ashariyyah dalam teologi.